2004
DOI: 10.1007/s00134-004-2255-z
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of lung emptying and expiratory resistance in mechanically ventilated patients with chronic obstructive pulmonary disease

Abstract: Patients with COPD exhibit a decrease in the rate of lung emptying toward the end of expiration due to an increase in Rrs. PEEP decreases Rrs, resulting in a faster and uniform rate of lung emptying.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
2
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 32 publications
(59 reference statements)
1
15
2
1
Order By: Relevance
“…In these circumstances, increasing external PEEP increases Vt for a given inspiratory pressure, will reduce pCO 2 and improve oxygenation. In obstructive disease, PEEP improves expiratory airflow, limits dynamic hyperinflation and improves alveolar ventilation 108 109. Dynamic hyperinflation may be suspected by a progressive fall in tidal volume with constant ventilator pressure settings (or, with volume control, an increase in inflation pressure) and by signs of increasing patient distress such as tachycardia and hypotension.…”
Section: Principles Of Mechanical Ventilationmentioning
confidence: 99%
“…In these circumstances, increasing external PEEP increases Vt for a given inspiratory pressure, will reduce pCO 2 and improve oxygenation. In obstructive disease, PEEP improves expiratory airflow, limits dynamic hyperinflation and improves alveolar ventilation 108 109. Dynamic hyperinflation may be suspected by a progressive fall in tidal volume with constant ventilator pressure settings (or, with volume control, an increase in inflation pressure) and by signs of increasing patient distress such as tachycardia and hypotension.…”
Section: Principles Of Mechanical Ventilationmentioning
confidence: 99%
“…Guttmann et al [10] reported an average Ƭ E of 0.60 seconds and Kondili et al [14] reported Ƭ E to be in the range of 0.70 seconds. In another study of COPD patients, Ƭ E varied inversely with PEEP; at end exhalation Ƭ E ranged up to 3.75 seconds on zero PEEP and up to 1.58 seconds on 10 cm H 2 0 PEEP [15]. …”
Section: Discussionmentioning
confidence: 99%
“…23 A vicious circle is created, and if the latter is not resolved, the patient gradually becomes exhausted until cardiovascular and respiratory collapse occurs in a way similar to that produced by tension pneumothorax. The only measure that has been shown to predict the complications of hyperinsufflation is the determination of end-inspiratory volume (V ei ) over functional residual capacity, calculating the total volume of gas exhaled in a patient with muscle paralysis after 60 s of apnea.…”
Section: Dynamic Hyperinsufflation and Auto-peepmentioning
confidence: 99%